Variation Analysis of Body Position Angle of the Race Athlete on Sprint - Zein Fiqri Habibie; Danang Ari Santoso; Arya T Candra (JUARA : Jurnal Olahraga, 2021)
This study aims to analyze the athlete's body position when the sprint race ahead of the opponent in minimizing air exposure (drag effect). The research method used was an experimental, descriptive quantitative approach. The analyzed angle variables are 45 °, 50 °, 55 ° with wind speed flow patterns at 3 points, namely front, top, and back. The results showed the force used to hold the turning angle at a 45 ° variation of 26739.593 N, a 50 ° angle variation of 28971.434 N, and at an interpretation of 55 ° of 30975.985 N. Based on the force used, it can be concluded that 45 ° angle variations are most effective in sprinting, because the position of the body at this angle narrows the air resistance on the bicycle racer so that it becomes light.